'As prostitutes, we control our bodies': perceptions of health and body in the lives of establishment-based female sex workers in Tijuana, Mexico. - Choudhury, Shonali M (Culture, health & sexuality, 2010)
Many studies of female sex work focus on HIV and other sexually transmitted infections because sex workers are considered bridges between high-risk and low-risk populations. The voices of female sex workers as they pertain to health issues are often lacking in the literature. This paper offers a feminist constructivist grounded theory study with establishment-based female sex workers in Tijuana, Mexico. Analyses of interviews with 20 women reveal that they are aware of the impact of their work on their bodies, but conceptualise their health holistically and not just in terms of HIV. They emphasise that working in the sex industry has implications for sexual health, non-sexual physical health and mental health. The paper concludes that in order for public health interventions to have more sustainable impact on the lives of female sex workers, they should take into account the voices of the women, including how they define their health. The findings suggest that public health professionals need to be more aware that female sex workers have agency and a desire to control their health and their bodies.
Keywords: Adult; Anecdotes as Topic; Attitude to Health; Coitus; Female; Health Status; Humans; Mexico; Prostitution; Questionnaires; Socioeconomic Factors; Urban Population; Women's Health; Women's Rights; Women, Working; Young Adult